Antioxidant properties of Klunzinger's mullet (Liza klunzingeri) protein hydrolysates prepared with enzymatic hydrolysis using a commercial protease and microbial hydrolysis with Bacillus licheniformis. (April 2022) - Rabiei, Sana; Rezaei, Masoud; Nikoo, Mehdi; Khezri, Mohammad; Rafieian-Kopai, Mahmoud; Anjomshoaa, Maryam
Antioxidant activity of Klunzinger's mullet ( Liza klunzingeri ) muscle hydrolysates obtained using Bacillus licheniformis fermentation and enzymatic hydrolysis was determined. Hydrolysates obtained after 6 days of fermentation with B. licheniformis showed the highest free radical scavenging activity, metal chelating ability and ferric reducing antioxidant power (FRAP) (P ≤ 0.05). Microbial fermentation led to a higher percentage of small peptides and higher solubility compared with Alcalase hydrolysis (P ≤ 0.05). Hydrolysates showing the highest antioxidant properties attenuated serum, liver, and kidney oxidative stress biomarkers in male Wister rats stressed by carbon tetrachloride (P ≤ 0.05). At 300 mg/kg oral administration, hydrolysates increased serum, renal, and hepatic total antioxidant capacity (TAC) (P ≤ 0.05) and reduced their elevated levels of malondialdehyde (MDA), nitric oxide (NO ), and serum liver enzymes (AST, ALP, and ALT) (P ≤ 0.05). The hydrolysates were able to ameliorate hepatic damage by reducing necrosis, fatty changes, and inflammation. Results showed the antioxidant and hepato-toxic protective activities of Klunzinger's mullet muscle hydrolysates obtained using microbial fermentation, which may, therefore, potentially be considered as a functional food ingredient.